Navigating Everyday Multiculturalism in the Culture Chats Writing Program: Observation from a Community Writing Workshop in Metro Vancouver - Li, Jing; Lawrence, Asmita (The Canadian Journal for the Study of Adult Education / La revue canadienne pour l’étude de l’éducation des adultes, 2023)
Adopting a “multiculturalism‑from‑below” approach and the perspective of public pedagogy, this study presents findings from a community‑based research project that looked into a group of immigrant women writers’ perceptions and experiences of everyday multiculturalism in the setting of a community writing workshop in Metro Vancouver, BC. Drawing on observation, interviews, and written artifacts, the findings highlight how the writers navigated on‑the‑ground multiculturalism through shared writing practices. These on‑the‑ground experiences reveal the disparities between the state multicultural ideology and the daily lived realities. The findings also demonstrate the pedagogical significance of the writing workshop as a critical praxis for transnational literary practices and socio‑cultural learning.